EFFECTIVE SELF-RELIANCE TEACHING MODEL USING VISUAL STORYTELLING FOR ELEMENTARY STUDENTS IN INDONESIA - Mujahidin, Endin; Ruhenda, Ruhenda; Nasution, Syamsuddin Ali (Unnes Science Education Journal, 2018)
The aim of this study was to design the visual storytelling teaching model addressed to self-reliance and implement it for increasing self-reliance of elementary students. This self-reliance study was focused on three main parameters which were self-command in daily activities, self-confidence and self-decision. This study was performed by survey, teaching materials designing and teaching delivery method implementation. The developed teaching materials were serial stories in animated pictures. Self-reliance was classified in three categories which were very good, good and enough. The result showed that average score of self-reliance of 1,805 students (from 6 schools) for three parameters above was in enough categories. After coaching by storytelling teaching model that involved 287 students and 12 teachers, the score of self-reliance were come up into good categories. The score increased 1.00 and 0.79 point for younger and older class respectively. This visual storytelling strategy was effective for self-reliance development in Indonesia and teachers should be involved intensively more than delivering only. Materials developed in this study are recommended to be applied as co-curricular activities or introduce in regular curriculum.The beneficial of this study is information on the importance of interesting teaching method and role of teacher in building self-reliance.